1996
DOI: 10.1113/jphysiol.1996.sp021805
|View full text |Cite
|
Sign up to set email alerts
|

The source of physiologically stimulated glutamate efflux from the striatum of conscious rats.

Abstract: 1. Glutamate in the extracellular compartment of the striatum of freely moving rats was monitored at 5 min intervals using microdialysis and an enzyme-based assay. 2. Basal levels of dialysate glutamate were 3-6 + 05 1uM. Local infusion through the dialysis probe of tetrodotoxin (TTX), cadmium chloride or magnesium chloride produced no reduction in basal levels of glutamate; with the latter two there was, instead, an increase. 3. Neuronal activation stimulated by induced grooming was accompanied by an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 36 publications
4
35
2
Order By: Relevance
“…4), which confirms the idea that acute tissue damage has a great influence especially on extracellular glutamate levels. Similar observations have been reported from microdialysis experiments in mammals under different experimental conditions (Miele et al, 1996;Moghaddam et al, 1997); however, the reasons for this large variability are unknown.…”
Section: Effect Of Nmda Receptor Activation On Glutamate and Taurinesupporting
confidence: 78%
“…4), which confirms the idea that acute tissue damage has a great influence especially on extracellular glutamate levels. Similar observations have been reported from microdialysis experiments in mammals under different experimental conditions (Miele et al, 1996;Moghaddam et al, 1997); however, the reasons for this large variability are unknown.…”
Section: Effect Of Nmda Receptor Activation On Glutamate and Taurinesupporting
confidence: 78%
“…The baseline concentration of glutamate we measured in the dialysate collected from the RVLM was in agreement with that reported by Caringi et al [2]. It was also in the same range as that detected in the brain of conscious rats [33]. Relevant to the present study, an increase in the extracellular glutamate concentration in the RVLM has been demonstrated to account for the attenuation of the BRR response to the central application of angiotensin II [49].…”
Section: Discussionsupporting
confidence: 81%
“…In support of the vesicular origin of glutamate in dialysate, basal or evoked levels of glutamate have been reported to be dereased in the presence of the fast sodium channel blocker, tetrodotoxin [9,36], or on infusion with calcium-free aCSF [9,34]. On the other hand, lack of a blunting effect by tetrodotoxin or calcium channel blocker on basal or evoked levels of glutamate in the brain has also been shown [33,41]. With our demonstration of site specificity in the PBN-induced increase in extracellular glutamate levels in the RVLM ( fig.…”
Section: Discussionmentioning
confidence: 94%
“…The task of detecting brain ECF Glu, however, is significantly more challenging than glucose monitoring, mainly because the baseline ECF concentration of Glu appears to be ≤5 M (Miele et al, 1996;Lada and Kennedy, 1996;Baker et al, 2002;Chen, 2005;Fillenz, 2005), although values as high as 15 M have been suggested (Kulagina et al, 1999), and compares to ∼500 M for ECF glucose (Boutelle et al, 1992;Lowry et al, 1998a). Thus, optimization of Glu sensitivity is critical for physiological applications, and we reported recently a significant enhancement of the linear region slope (LRS) for Glu, by incorporating the polycation polyethyleneimine (PEI) in these PPD-based biosensors (Pt/PEI/GluOx/PPD) (McMahon et al, 2006b The protein immobilizing agent (Tang et al, 1998) and stabilizer (Bryjak, 1995;Andersson and Hatti-Kaul, 1999), PEI, has been used previously in biosensors for a number of analytes, including Glu (Belay et al, 1999;Rahman et al, 2005;Varma et al, 2006).…”
Section: E-mail Address: Robertoneill@ucdie (Rd O'neill)mentioning
confidence: 99%